Exploring medieval Britain - Millea, N (2008)
The Gough Map of Great Britain is one of the Bodleian Library’s most significant cultural and cartographic treasures: it is the earliest surviving modern map of Britain, showing a recognizable coastline, dating from around 1360, and until recently identified as the first road map of the country. This paper will examine how the map library has recently been pivotal in encouraging new research on an enigmatic object of unknown origin and function. The intention is to demonstrate that not only is the map library the custodian of this particular artefact, but to emphasize how its rôle extends to identifying the map’s research potential, facilitating its academic exploitation, attracting collaborators, and disseminating information. The map’s known history and content will be explained before outlining an agenda for future academic discovery. Based on an initial scan and desire for additional textual support material both driven from the map library, this paper will examine progress made within the Bodleian and beyond, working alongside multi-disciplinary colleagues from around the World to ascertain why the Gough Map was made, for whom was it made, and why was it made. It will be demonstrated that the map library has been the focus around which all subsequent investigation has been concentrated, leading the drive for future co-ordinated research, conservation, publications, and a possible travelling exhibition.